The Subthalamic Nucleus. - Heida, T.; Marani, Enrico; Usunoff, K. G. (Advances in Anatomy, Embryology and Cell Biology, 199.)
Part II starts with a systemic model of the basal ganglia to evaluate the position of the STN in the direct, indirect and hyperdirect pathways. A summary of in vitro studies is given, describing STN spontaneous activity as well as responses to depolarizing and hyperpolarizing inputs, and high frequency stimulation. STN bursting activity and the underlying ionic mechanisms are investigated. Deep brain stimulation used for symptomatic treatment of Parkinsona (TM)s disease is discussed in terms of the elements that are influenced and its hypothesized mechanisms. This part of the monograph pays at.